Carbon Sequestration Dynamics in Urban-Adjacent Forests: A 50-Year Analysis - A. A. Vais; P. V. Mikhaylov; V. V. Popova; A. G. Nepovinnykh; V. N. Nemich; A. A. Andronova; S. K. Mamedova (Salehan Institute of Higher Education, 2023)
Achieving carbon neutrality is crucial for urban ecosystems. Forests growing near cities largely determine the state of the environment in urban areas. The aim of the present research is to assess the carbon productivity dynamics in forests near Krasnoyarsk (a large industrial center) over a 50-year period in terms of carbon sequestration and conservation. The study was based on forest inventory conducted in Karaul'noe Forestry in 1972, 1982, and 2002 and forest inventory covering six forest compartments in 2022. The forest covers 3980 ha and consists of 52 forest compartments. The analysis was based on the assessment of carbon productivity dynamics and followed four levels of principles: forestry, structure, forest compartment, and forest stand. The research was based on forest fund dynamics, analyzing methods, long-term forest inventory, assessing carbon stock, and growing stock dynamics. Pine is the dominant forest-forming species that absorbs the most carbon in the study area. Pine is long-lived, covers a vast area, and has the highest carbon sequestration potential. At the forest structure level, the predominant carbon pools are mid-late successional and late successional stands dominated by pine, birch, and aspen. Forest compartment-level analysis revealed three trends in carbon sequestration: carbon balance, a decrease in carbon sequestration, and an increase in carbon sequestration. Notably, the prevailing trend is determined by changes in carbon sequestration by dominant forest-forming species (pine). Forest stand-level analysis showed that stands have become more and more uneven-aged. About 65% of total carbon stock is concentrated in mid successional, mid-late successional and late-successional stands, and 35% in young stands. The carbon sequestration rate decreases in forests with age. However, pine forests increase biological productivity and continue to successfully sequester carbon. Deciduous forests have lost their carbon sequestration potential, and the area they occupy is currently decreasing in the study area. The development of the young generation in pine stands suggests that the carbon sequestration potential in forests growing near the city will not decrease and may even increase due to climate change.Â Doi: 10.28991/CEJ-2023-09-09-08 Full Text: PDF